Diagnosis and surgical decision-making of a 46, XX ovotesticular disorders of sex development patient: a case report - Hanxing Zhao; Zhixing Chen; Zhixing Chen; Baoyun Wang; Zhenyu Zhang; Zhenyu Zhang; Zhengyong Li; Zhengyong Li (Frontiers in Surgery)
BackgroundOvotesticular disorder of sex development is a rare form of disorder of sex development that manifests as ovotestis in individuals. The precise diagnosis and the choice of surgical procedures are still in conflict condition due to the rarity of the disease, diverse clinical presentations, and the lack of evidence-based medical studies on postoperative outcomes.Case presentationWe present a 46, XX ovotesticular disorder of sex development case, aged 19, with Prader stage IV virilization who underwent feminizing genitoplasty surgery. Our surgical strategy prioritized the patient's genitourinary function restoration and cosmetic reconstruction achieved satisfactory results. We attribute the success of the treatment to the systematic diagnostic process and individualized surgical planning.ConclusionThe purpose of this article is to provide an evaluation protocol for the ovotesticular disorder of sex development, improving the diagnostic rate and providing some fresh ideas for surgical management.